Dasatinib dose optimisation based on therapeutic drug monitoring reduces pleural effusion rates in chronic myeloid leukaemia patients. (30th June 2021) - Rousselot, Philippe; Mollica, Luigina; Guilhot, Joëlle; Guerci, Agnès; Nicolini, Franck E.; Etienne, Gabriel; Legros, Laurence; Charbonnier, Aude; Coiteux, Valérie; Dartigeas, Caroline; Escoffre‐Barbe, Martine; Roy, Lydia; et al.
Summary: Dasatinib is a second‐generation BCR‐ABL1 tyrosine kinase inhibitor approved for patients with chronic myeloid leukaemia (CML). Dasatinib 100 mg per day is associated with an increased risk of pleural effusion (PlEff). We randomly evaluated whether therapeutic drug monitoring (TDM) may reduce dasatinib‐associated significant adverse events (AEs) by 12 months (primary endpoint). Eligible patients started dasatinib at 100 mg per day followed by dasatinib (C)min assessment. Patients considered overdosed [(C)min ≥ 3 nmol/l) were randomised between a dose‐reduction strategy (TDM arm) and standard of care (control arm). Out of 287 evaluable patients, 80 patients were randomised. The primary endpoint was not met due to early haematological AEs occurring before effective dose reduction. However, a major reduction in the cumulative incidence of PlEff was observed in the TDM arm compared to the control arm (4% vs. 15%; 11% vs. 35% and 12% vs. 39% at one, two and three years, respectively ( P = 0·0094)). Molecular responses were superimposable in all arms. Dasatinib TDM during treatment initiation was feasible and resulted in a significant reduction of the incidence of PlEff in the long run, without impairing molecular responses. (NCT01916785; https://clinicaltrials.gov ).